Association between serum vitamin D concentrations and inflammatory markers in the general adult population - Mellenthin, Liesa; Wallaschofski, Henri; Grotevendt, Anne; Völzke, Henry; Nauck, Matthias; Hannemann, Anke (Metabolism, clinical and experimental, 2014)
In recent years links among vitamin D deficiency, inflammation and cardio-metabolic disease were proposed. As information regarding the associations between vitamin D and inflammatory markers in the general population is sparse, we investigated the associations of 25-hydroxy vitamin D [25(OH)D] with high-sensitivity C-reactive protein (hs-CRP), fibrinogen and white blood cell count (WBC). The study population comprised 2723 men and women aged 25–88 years from the first follow-up of the Study of Health in Pomerania. Analyses of variance, linear and logistic regressions were performed to assess the associations between 25(OH)D and the three inflammatory markers. The models were adjusted for age, sex, waist circumference, diabetes mellitus, dyslipidemia, anti-inflammatory medication and month of blood sampling. The association between 25(OH)D and WBC was assessed separately in smokers (n=718) and non-smokers (n=2005) as effect modification was observed. We detected a U-shaped association between 25(OH)D and hs-CRP with a nadir of 21–25ng/ml in fully-adjusted linear regression models with restricted cubic splines (p<0.01; p’<0.01). We further detected an inverse association between 25(OH)D and fibrinogen (p<0.01). In addition, there was an inverse association between 25(OH)D and WBC in smokers (p=0.02) but no association in non-smokers (p=0.73). Our study confirms a potential role of 25(OH)D in chronic inflammation. Yet, different inflammatory biomarkers are differently associated with 25(OH)D. Beneficial effects of increasing 25(OH)D were observed for fibrinogen and WBC (in smokers only). In contrast, the U-shaped association between 25(OH)D and hs-CRP indicates that ever-increasing 25(OH)D concentrations may also be related to proinflammatory states.